Bismuth‐based candidates for topological insulators: Chemistry beyond Bi2Te3. Issue 1 (12th February 2013) - Isaeva, Anna; Rasche, Bertold; Ruck, Michael
Abstract <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text> The present contribution considers chemical aspects relevant for established and candidate topological insulators (TIs) based on the element bismuth. We provide an overview of selected bismuth‐containing compounds with topological protection, place them among structurally related compounds and, proceeding from the comparison, propose further families and guidelines for the search of new candidate TIs. Owing to the unique electronic properties and structural flexibility, bismuth demonstrates an overwhelming diversity of structural motifs, including low‐dimensional ones. Bismuth acts both as an electron donor and acceptor interacting with other elements, thus initiating a refined interplay of electron delocalization and localization that results in a wide range of properties – from an insulator or a semiconductor to a metal or a semimet al. Due to the bonding abilities of Bi 6p‐orbitals an isolated pure‐bismuth layer is bound to be corrugated. Yet compounds exist with planar decorated honeycomb nets of bismuth and transition‐metal atoms that allow for testing theoretical predictions that nets with such geometry could support a TI phase. (© 2013 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)